Facilitators and Barriers Highlighted by On-Campus Service Providers for Students Seeking Mental Health Services - MacDonald, Hana; Lisnyj, Konrad; Papadopoulos, Andrew (Canadian Journal of Higher Education, 2022)
The prevalence of mental illness is increasing among post-secondary students. Despite more mental health services being of-fered within post-secondary institutions, uptake among students remains suboptimal. This study aimed to examine facilitators and barriers for students seeking mental health services through service providers’ perspectives. Twenty-four semi-structured interviews were conducted at a southwestern Ontario post-secondary institution and were analyzed using thematic analysis using NVivo. Facilitators revealed include strengthening communication techniques; improving equity, diversity, and inclu-sion; increasing social media promotion; and providing incentives. Barriers identified include fear of judgement, time con-straints, individual perceptions of the need for services, unawareness, and higher-level barriers such as lowered capacity of staff and physical resources. These facilitators and barriers should be used in tandem with the Theory of Planned Behaviour to help improve uptake and effectiveness of campus mental health services.